Detection of Oil in Water Using Photodiode and Internet of Things - Nur Nazifa Che Samsuria; Wan Zakiah Wan Ismail; Mior Fakhrul Hazim Mior Abdul Halil; Nor Azlina Ab Aziz; Anith Khairunnisa Ghazali; Wan Maryam Wan Ahmad Kamil (Penerbit UTHM, 2026)
Indexed by WOS/ERA/MyCite